ENHANCING LEARNER AGENCY THROUGH SELF-DIRECTED LEARNING: A CASE STUDY AT TAY NGUYEN UNIVERSITY (Isagoge - Journal of Humanities and Social Sciences, 2025)
In the current context of higher education reform, fostering learner agency plays a pivotal role in developing a workforce equipped with independent thinking, creativity, and adaptability to the challenges of a knowledge-based society. This article focuses on analyzing the relationship between self-directed learning (SDL) and the development of learner agency among students at Tay Nguyen University (TNU) - a regional institution with a high proportion of ethnic minority students. This study draws on established theoretical foundations and empirical data from a stratified sample of 397 students across disciplines, supplemented by 12 semi-structured interviews, to examine how SDL contributes to the development of learner agency at TNU. It thereby underscores the essential role of SDL in cultivating core attributes of learner agency, such as autonomy, reflexivity, and a sense of social responsibility. The research findings contribute to proposing practical educational directions that are responsive to the distinctive needs of regional universities and aligned with the broader goal of fostering holistic human development.